Recovery of copper (II) and chromium (III,VI) from electroplating-industry wastewater by ion exchange - Yalçin, S; Apak, R; Hizal, J; Afsar, H (MARCEL DEKKER INC, 2001)
Two laboratory-scale separation processes have been developed for the recovery of copper (II) from acidic and cyanide-containing alkaline wastewater of electroplating industries. Acidic bath wastes were treated with Dowex 50X8, a strongly acidic cation-exchange resin, and the retained copper was eluted with H2SO4. The cyanide-containing alkaline bath waste was first oxidized with excessive hypochlorite, then neutralized, and recovered by the use of Amberlite IRC-718 chelating resin. Copper was eluted with H2SO4. The two different valencies of chromium have been recovered from electroplating-industry wastewater by different separation processes: The predominant valency, Cr(VI), was retained on a strongly basic Dowex 1X8 resin and eluted with a NaCl and NaOH solution. Alternatively, Cr(III), either existing originally in electroplating-industry waste-rinse mixtures or converted from Cr(VI) by reduction with Na2SO3, could be recovered by a weakly acidic Amberlite IRC-50 resin and eluted with a solution containing H2O2 and NaOH. Where plating industry wastes contain high levels of organic contamination, Cr(VT) would be naturally reduced to Cr(DI) upon acidification, and it may be more economical to recover all chromium as Cr(TII).
Keywords: copper (II); chromium (VI); chromium (III); recovery; removal; electroplating-industry wastewater; ion exchange; wastewater treatment; TANNERY WASTES; HEAVY-METAL; WATER; SEPARATION; RESINS; PRECONCENTRATION; SPECIATION; EFFLUENTS; CR(III); Chemistry; Engineering